The Europeanization of National Policies and Politics of Immigration Between Autonomy and the European Union - Faist, T.; Ette, A.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2007)
The Europeanization of National Policies and Politics of Immigration is the first cutting-edge volume presenting a comparative empirical investigation on the impact of the EU on migration policy at national level. Revealing striking differences, this collection examines traditional member states, new member states as well as non-member states.
Keywords: European Union; Europe—Politics and government; Political sociology; Sociology; Emigration and immigration; Political science; European Union Politics; European Politics; Political Sociology; Sociology, general; Migration; Political Science